Keterkaitan Profitabilitas dan Leverage dalam Manajemen Laba - Arwan Gunawan; Jouzar Farouq Ishak; Arianto Wisnu Prabowo (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Earnings management practices are driven by profitability and leverage factors. Profitability describes the company’s ability to generate profits within a certain period through asset management. The higher the level of profitability, the higher the company’s performance in generating profits. Conversely, if the profitability obtained is low, it will trigger earnings management. Leverage has the aim of measuring the company’s ability to pay debts or measuring how much it owes on assets owned by the company. The higher the level of leverage the company will provide an indication that the company will face difficulties in its debt agreements. The high leverage ratio of the company will trigger the company to carry out earnings management. The purpose of this study is to partially examine the relationship between profitability and leverage in earnings management. The method used is descriptive analysis, including: calculation of profitability ratio, calculation of leverage ratio, and determination of earnings management using the Modified Jones Model calculation steps and hypothesis testing using regression equations. The results of this study indicate that profitability and leverage are related to earnings management. This relationship supports and encourages investors’ decision making to choose issuers that can provide optimal profits, which is also related to increasing value of the firm.